Pennogenin Exerts Anti-inflammatory and Anti-nociceptive Effects in Several Models of Inflammation and Nociception in Mice - Tao, Yan; Cai, Nan; Zhang, Juxia; Zhao, Yaoping; Zhou, Yan; Liu, Pengfei (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: The nociceptive pain is a fundamental sensory response that works as a crucial protective mechanism for the human body. Chronic pain constitutes a substantial public health issue, impacting millions of individuals globally. Objectives: The present work focused at investigating the beneficial activities of pennogenin against nociceptive and inflammatory models induced by various stimuli. Materials and Methods: In the present study, the Swiss mice were utilized and the nociception was produced in the mice using various chemical stimuli and thermal stimuli techniques. The experimental mice were treated with the pennogenin at 5, 10 and 15 mg/kg concentrations before the stimuli induction. The anti-inflammatory activities of the pennogenin were examined using carrageenan-triggered inflammation model in mice. The inflammatory cytokine levels were assessed using commercial kits. Results: The results of this work proved that the pennogenin treatment effectively elevated the reaction time on hot plate, enhanced the response time in the tail immersion time in hot water, reduced the writhing numbers and decreased licking responses in the mice. Moreover, pennogenin treatment also reduced the carrageenan-stimulated paw edema, decreased the peritoneal penetrations of leukocytes and pro-inflammatory cytokine levels in the experimental mice, which indicates the anti-inflammatory potentials of the pennogenin. Conclusion: In conclusion, the current findings highlighted the anti-inflammatory and antinociceptive properties of pennogenin in several heat- and chemically-produced pain and inflammation models.
Keywords: Capsaicin; Carrageenan; Hot plate method; Inflammation; Pain response; Pennogenin